(untitled) (El Taco en la Brea, 2025)
The question about violence runs through the history of Argentine literature. This essay asks about this problem based on the review of four recent novels: It is not a river, by Selva Almada (2021); The Desarmadero, by Eugenia Almeida (2022); Outlet, by Laura Liébana (2022) and Cometierra, by Dolores Reyes (2020). The text brings into conflict the so‒called interrogative narratives of violence (capable of tensioning the dominant discourses on violence, crime, and illegalities, from the power of literature’s question) and the affirmative narratives of violence (hegemonic stories that crystallize its meaning from the hegemonic media). From this counterpoint, the temporal dimension, alterities, spaces, and multiple meanings of violence are reviewed. Finally, some reflections are presented on the potential of literary fiction to provoke the social sciences from its power of doubt.